2015
DOI: 10.1093/jrr/rrv051
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of radiation dose on the behavioral patterns among school children: a retrospective analysis 18 to 20 months following the 2011 Fukushima nuclear incident in Japan

Abstract: After radioactive incidents, the exposure risk in daily activities among children is a major public concern. However, there are limited methods available for evaluation of this risk, which is essential to future health risk management. To this end, this study assessed the relationship between behavioral patterns of school children and radiation exposure for a period of 18–20 months following the 2011 Fukushima nuclear incident. The assessed population comprised 520 school children from Minamisoma city, located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…The methods of these measurements have been documented in detail in a previous study [40]. All monitored results are publicly available [41].…”
Section: Methodsmentioning
confidence: 99%
“…The methods of these measurements have been documented in detail in a previous study [40]. All monitored results are publicly available [41].…”
Section: Methodsmentioning
confidence: 99%
“…Improving dose conformity for IMPT is important, because it may decrease the risk of radiation pneumonitis [ 31 ]. Although IMPT and CIRT, compared with 3D–CRT, have been shown to improve target volume coverage when multiple fields are used, IMRT has been shown to have better dose conformity and homogeneity than passively scattered PT [ 17 22 ]. Our study comparing IMPT and VMAT demonstrated similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…PT has traditionally been shown to decrease the low dose volumes in the lungs [ 15 22 ]. IMPT, and especially IMPT arcs, compared with passively scattered PT, may further decrease the normal lung dose [ 16 , 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneous nature of ambient dose equivalent rates around roads raises the question of how to apply VBM results above roads for calculating annual effective doses (mSv/y) to the public. For Fukushima residents, annual effective doses are typically accrued inside homes, schools and offices (Naito et al, 2015;Nomura et al, 2016;Naito et al, 2016). For outdoor workers, such as farmers and workers in the decontamination, forestry and construction sectors, doses received outdoors away from roads are important.…”
Section: The Portable Monitoring Systems Kurama (Kyoto University Radmentioning
confidence: 99%